Current status of research of al-Farabi`s heritage abroad - Tuleubayeva S.A., S А (Journal of Oriental Studies, 2016)
The paper attempts to provide an overview and analysis of Farabi`s studies abroad at the present stage, in particular, the achievements of Western, Arab and Iranian scientists.